Enhancing Silk Production: Impact of Milk Fortified Mulberry Feed on Silkworm (Bombyx mori L.) Growth and Cocoon Quality - S, Nivetha; A.S., Maheswari; C, Elakiya; R, Gowri; A, Kalaivani (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Enhanced silk production measures directly contributes to the economic upliftment of farmers engaged in Sericulture. Fortification of mulberry leaves to enhance silk production in silkworms is a promising approach to boost the quality and quantity of silk. By enriching mulberry leaves with additional nutrients such as proteins, vitamins, and minerals, the overall health and development of silkworms can be significantly improved. Therefore, this study investigates the efficacy of fortified mulberry feed on the growth and cocoon quality of Bombyx mori L. by using commercially available milk samples. The research aims to enhance the nutritional status of mulberry leaves through milk fortification to improve the biological characteristics and silk production of silkworms. Various milk samples, including Aavin, Arokya, and Bovine, were used to fortify the mulberry leaves fed to the monophagous silkworm larvae. The results of the present study demonstrated a significant increase between the control and the experimental setups—MST 1, MST 2, and MST 3. Notable improvements were observed in cocoon weight, pupal weight, and shell weight across the experimental categories compared to the control, with values recorded as follows: cocoon weight (1.15±0.10 to 1.25±0.14), pupal weight (0.86±0.13 to 0.96±0.11), and shell weight (0.21±0.07 to 0.27±0.23). These findings highlight the efficacy of milk fortification in significantly enhancing cocoon production, highlighting its potential to improve the efficiency and productivity of the sericulture industry. Further, these findings suggest that milk fortification of mulberry leaves could be a practical and effective method to boost silk production and improve the livelihoods of farmers engaged in sericulture.